Preservice teachers' voices while learning to teach - Abd Rahman, Fadzilah; Scaife, Jon; Yahya, Nurul Aini; Ab Jalil, Habibah (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
An attempt to facilitate pre service teachers learning which is attuned with their learning needs raises questions regarding how pre service teachers learn to teach. As learning to teach is developmental and a lifelong process, it puts heavy demands of a cognitive, affective and performance nature upon the pre service teachers (PSTs). It is a complex process as information that is useful to experienced teachers may not have the same value to the beginners (Arends, 2004). An understanding of the process of learning to teach may help to clarify the role of teacher education programmes especially at the pre-service level (Feiman-Nemser and Remillard, 1996). For instance, what do PSTs come to know about teaching and learning? How in the process of becoming teachers do PSTs replace notions about teaching and learning with practical knowledge of subject matter, pedagogy, learners, contexts, and learning that can inform their teaching judgments and actions? This paper discusses finding from a study conducted at a university department of educational studies in England. The study focused on how pre service teacher develop their knowledge of teaching throughout their teaching practice period.